Protein suppresses both bitterness and oleocanthal-elicited pungency of extra virgin olive oil - Catherine Peyrot des Gachons (Nature Portfolio, 2021)
Abstract The Mediterranean diet, considered one of the healthiest in the world, is characterized in part by the major source of its fat, which is extra virgin olive oil (EVOO). Among the health benefits of consuming EVOOs is the presence of phenolic compounds, which have been shown to lower the incidence of coronary heart disease and are suspected of providing many other health benefits. These phenolic compounds also contribute to the flavor of EVOO, adding both specific pungency in the throat and bitter notes that are valued by connoisseurs but reported to be unpleasant by naïve consumers. Here, we demonstrate that some food-derived proteins, specifically from egg yolks and whey, when added to pungent and bitter EVOOs, reduce or even eliminate both the throat pungency and bitterness. The sensory loss is proportional to the food protein additions. Thus, when used in various foods recipes (e.g. mayonnaise), pungent and bitter EVOOs may lose their pungent and bitter characteristics thereby rendering them more palatable to many consumers. This sensory reduction might also indicate interaction between the proteins and the phenolic compounds, which, if confirmed, would raise the question of whether the bioactivities of EVOO phenolics remain unchanged when consumed with and without protein-containing foods.